The effect of halal certification, product quality and word of mouth on consumer loyalty - Amalia, Putri; Rahman, Taufiqur (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This study aims to identify the influence of halal certification, product quality, and word of mouth on consumer loyalty at V-Fie Bakery. This research aims to discover the factors that affect consumer loyalty and provide an overview of business actors when facing increasingly fierce market competition. The research method used is quantitative research. One hundred respondents determined the sample. The sampling technique in this study uses probability sampling. Data was collected through a questionnaire and analysis using regression. The results of this study state that halal certification does not have a significant effect on consumer loyalty. On the other hand, product quality and word of mouth significantly affect consumer loyalty at V-Fie Bakery. Simultaneously, halal certification, product quality, and word of mouth affect consumer loyalty. Public interest statements This research is helpful for business people, especially in the current era of globalization, by increasing awareness and trust in halal products, carrying out more effective marketing strategies, increasing product competitiveness, and providing important insights for consumers in knowing the factors that affect loyalty or trust. In addition, this research plays an important role in encouraging economic growth and strengthening the food industry to be more developed and meet consumer expectations.